Pemphigus Foliaceus in A Potato Donut Seller: A Case Report - Rizky Alhuda Rachman; Dewi S. Soemarko (ILUNI MKK FKUI and PRODI MKK FKUI, 2023)
Background: Pemphigus foliaceus is a condition of a rare and potentially life-threatening autoimmune blistering skin disease, thought to be caused by circulating autoantibodies against desmoglein-1 (Dsg-1), a glycoprotein with an integral role in maintaining intercellular adhesion between keratinocytes. Pemphigus foliaceus primary lesions generally manifest as erythematous papules, plaques, and erosions with the addition of scaly crusts as secondary lesions. Immunosuppressant is the mainstay therapy for pemphigus foliaceus. This case report describes the case of a female patient who worked as a potato donut seller with pemphigus foliaceus and analyzes the relationship between her disease and work.Case Presentation: A 31-year-old woman presented with a history of itchiness, redness, and burning sensation on her face, followed by the appearance of vesicles on her face, spreading to the back, arms, and legs. The patient worked as a potato donut seller and encountered numerous potential hazards. Upon further examination, the patient was diagnosed with pemphigus foliaceus. Discussion: Establishing an occupational disease requires a seven-step method, taking into account the clinical diagnosis, occupational, individual, and other exposures outside of work. In this case, neither occupational, individual, nor other environmental risk factors of pemphigus foliaceus was found. Conclusion: There are no substantial evidence that occupational exposures as a potato donut seller cause or exacerbate the patient’s diagnosis of pemphigus foliaceus. The patient’s innate genetic susceptibility remains the main factor contributing to her diagnosis.